2018
DOI: 10.3390/rs10060866
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Lake Area of Tonle Sap: Possible Linkage to Runoff Alterations in the Lancang River?

Abstract: Tonle Sap Lake is the largest freshwater lake in Southeast Asia. Water development infrastructures are increasingly being constructed in the Lancang-Mekong River Basin, which is a major concern considering its potential impact on Tonle Sap Lake. This study aimed to investigate variations in the area of the lake and discuss their possible linkage to runoff alterations in the Lancang River (Upper Mekong) by comparing runoff at the Yunjinghong hydrological station before and after significant changes in runoff tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…The permanent lake extends over of a large territory towards the Northwest of Cambodia, with dimensions of 75 km x 32 km. It comprises a small part in the Southeast of the domain with dimensions of 35 km x 28 km [35,36]. The lake and its floodplains form the largest freshwater source in Southeast Asia [34].…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…The permanent lake extends over of a large territory towards the Northwest of Cambodia, with dimensions of 75 km x 32 km. It comprises a small part in the Southeast of the domain with dimensions of 35 km x 28 km [35,36]. The lake and its floodplains form the largest freshwater source in Southeast Asia [34].…”
Section: Study Areamentioning
confidence: 99%
“…These differences between the two results can be attributed to the fact that [50] performed their simulations based on data from 2002, that is a particular year with high flooding and two peaks in the whole Mekong basin. Moreover, the data used by [50] were not affected by the operation of the hydropower cascade in China that began in 2008 [35].…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, USGS stated that band 7 for MSS, band 5 for OLI/TIRS, and band 4 for TM, ETM+ were advantageous for mapping shorelines. In this paper, satellite images obtained Ji et al (2018) investigated the changes in the surface area of Tonle Sap Lake in Cambodia from 2000 to 2014. Authors stated that water surface area showed an overall decreasing trend during this period.…”
Section: Figure 2 Temporal Change In Water Surface Areamentioning
confidence: 99%
“…Monitoring of spatial and temporal changes using satellite images has globally become crucial for better understanding and explaining of environmental changes in the reservoirs. Spatial and temporal changes of water surface in lakes and reservoirs were monitored by several scientists (Sidle et al, 2007;El-Asmar et al, 2013;Abu-Faraj et al, 2014;Hossen et al, 2018;Ji et al, 2018;Tan et al, 2018;Yapiyev et al, 2019). There are few researches on change monitoring of water surface in lakes and reservoirs in Turkey (Akar et al, 2002;Reis and Yılmaz, 2008;Durduran, 2010;Avdan et al, 2013;Bahadır, 2013;Battal et al, 2016;Erener et al, 2016;Yücel and Turan, 2016;Sarp and Ozcelik, 2017;Topuz and Karabulut, 2018).…”
Section: Introductionmentioning
confidence: 99%